ILMU PENGETAHUAN DAN PEMBAGIANNYA MENURUT IBN KHALDUN - Rahmat Effendi (TAJDID: Jurnal Ilmu Ushuluddin, 2019)
Although he also discussed science with various branches and scope, so that he was known as an expert in the discourse of science in Islam, Ibn Khaldun was still often positioned as a sociologist rather than a philosopher. Ibn Khaldun's position as a philosopher will be tested in this article. This article further examines Ibn Khaldun's thinking about science by putting forward his views, divisions, and scope. On several occasions, Ibn Khaldun classifies knowledge in broad terms on the science of naqliyyat and ‘aqliyyat. This classification is contained in the magnum opus, namely Muqaddimah. The discourse proposed by Ibn Khaldun in this division of knowledge received criticism from Ibn Khaldun, as well as his defense. What Ibn Khaldun has done has shown that knowledge in the world needs to be known and mastered by Muslims. That way can deliver Muslims to be people who are in control of this world. Meskipun turut membahas ilmu pengetahuan dengan beragam cabang dan cakupannya, sehingga dikenal sebagai ahli dalam wacana ilmu pengetahuan dalam Islam, Ibn Khaldun masih sering diposisikan sebagai sosiolog dibandingkan filosof. Posisi Ibn Khaldun sebagai filosof akan diuji dalam artikel ini. Artikel ini menguji lebih jauh pemikiran Ibn Khaldun mengenai ilmu pengetahuan dengan mengedepankan pandangan, pembagian, dan ruang lingkupnya. Dalam beberapa kesempatan Ibn Khaldun mengklasifikasikan ilmu secara garis besar pada ilmu naqliyyat dan ilmu ‘aqliyyat. Klasifikasi ini jelas tertuang dalam magnum opus yaitu Muqaddimah. Diskursus yang diajukan Ibn Khaldun dalam pembagian ilmu ini mendapatkan kritikan oleh Ibn Khaldun, disamping pula pembelaan. Apa yang dilakukan Ibn Khaldun telah menunjukkan bahwa ilmu pengetahuan yang ada di dunia perlu diketahui dan dikuasai umat Islam. Dengan begitu dapat mengantarkan umat Islam menjadi umat yang memegang kendali atas dunia ini.